Sustainability and islamic environmental principles for agribusiness - Spadotto, Anselmo Jose [UNESP]; Campos e Sant Anna, James Eduard (Editora Dom Helder, 2020)
When seeking the practice of environmental sustainability in relation to agribusiness between different cultures, the theme can become complex, requiring guiding principles. This research is justified because agribusiness, in relation to environmental sustainability, is an extremely important subject that involves complex legal relationships. In this context, the hypothesis proposed here was that it would be possible to develop Islamic environmental principles for agribusiness. Based on this hypothesis, it was possible to draw as objective of the present research “to analyze interfaces between the Islamic and Brazilian environmental law seeking to identify and characterize Islamic environmental principles for agribusiness”. This research was classified as qualitative, being applied the deductive logic in the comparison of the intermediate results and the inductive logic for the inferences. In conclusion, were found these Islamic environmental principles to realize agribusiness: what is expressly forbidden by Allah in the Holy Qur’an and Sunna will not be done in agribusiness; what is harmful to the body will not be consumed or marketed; what Islamic fatwas condemned is rejected in agribusiness; animals are considered rational beings, but with limited rationality; the product coming from the suffering of animals does not serve as food and for another application; preference should be given to the least damaging of the natural environment.
Sustentabilidade e princípios ambientais islâmicos para realizar agronegócio
Keywords: Environmental Law; Food; Halal; Islamic Law; Muslim